STRANGE FRUIT, Chekhov's The Cherry Orchard in the Deep South. Issue 2 (2nd July 2016) - Dykes, Steven
Abstract: This article will attempt to analyse the creative and technical process of the site-specific production of the play Strange Fruit at Rose Bruford College of Theatre and Performance in April 2015, and how the student company found that transposing Anton Chekhov's The Cherry Orchard from rural Russia to the cotton fields of Dixie heightened their awareness of just how much civil unrest and human bondage dictate the characters' relationships with each other, the family estate and the land itself. What follows is an analysis of how the transplanting of the location from Russia to America; the adaptation of the text for a site-specific, multi-audience promenade production; and a strict adherence to Chekhov's insistence that the comedic and farcical elements of the play be given their full due, all contributed to fulfilling the project's educational brief of training student performers, designers and technicians in the conventions of "ensemble" theatre. The particular focus lies in the portrayal of African-American characters and their Russian counterparts, drawing on biographical sources highlighting Chekhov's personal experience of the legacy of serfdom and historical accounts by former slaves of the Deep South in the immediate post-Civil War years. To download the e-pub text of Strange Fruit and to view a photographic record of the production go tohttp://www.stevendykesplaywright.com/showcase/strange-fruit/ .